Double-bundle ACL reconstruction: Novice surgeons utilizing computer-assisted navigation versus experienced surgeons. (10th May 2013) - Anthony, Chris A.; Duchman, Kyle; McCunniff, Pete; McDermott, Scott; Bollier, Matthew; Thedens, Dan R.; Wolf, Brian R.; Albright, John P.
Abstract: Purpose : Anatomic double-bundle ACL reconstruction presents a unique technical challenge for surgeons, requiring precise placement of multiple tunnels in a relatively small area. As the necessity of anatomic reconstruction has been stressed throughout the literature, developing a method to consistently improve the accuracy and precision of tunnel placement is essential. We aimed to investigate whether computer-assisted navigation allows novice surgeons to place double-bundle ACL tunnels with a similar degree of accuracy to experienced surgeons operating without computer assistance. Methods : A novice surgeon group comprising three medical students performed double-bundle ACL reconstruction using passive computer-assisted navigation in 11 cadaver knees. Their individual results were compared to those of three experienced orthopaedic surgeons, each performing the identical procedure without the use of computer-assisted navigation in 9 cadaver knees. Results and conclusion : There were no significant differences in placement of either the AM or PL tunnels on the tibial plateau between the novice surgeons using computer-assisted navigation and the experienced surgeons. However, on the lateral femoral condyle, the novice surgeons placed the AM and PL tunnels significantly more anterior along Blumensaat's line, on average, compared to the experienced surgeons.